2020
DOI: 10.29252/jommid.8.3.84
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Typhoidal Salmonella Infections and Associated Risk factors in Kaduna Metropolis, Nigeria

Abstract: Salmonella species Salmonella typhi and Salmonella paratyphi, types A, B, and C are the causative agents of enteric fever. This disease continues to pose a severe threat to public health, especially in developing countries. This study investigated the prevalence of typhoidal Salmonella infections and the associated risk factors in Kaduna Metropolis, Nigeria. Methods: A questionnaire was used to obtain information from 250 patients attending four selected government hospitals and 50 healthy individuals as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The remaining 380 negative blood cultures are clinically presumptive of typhoid fever. Comparatively similar studies in Nigeria by Omotola et al (2020), Ethiopia by Habte et al (2018) and Egypt by Srikantiah et al (2006) have been reported. A study by Sharanya et al (2016) in India reported a higher culture-confirmed Salmonella Typhi (16%).…”
Section: Discussionsupporting
confidence: 68%
“…The remaining 380 negative blood cultures are clinically presumptive of typhoid fever. Comparatively similar studies in Nigeria by Omotola et al (2020), Ethiopia by Habte et al (2018) and Egypt by Srikantiah et al (2006) have been reported. A study by Sharanya et al (2016) in India reported a higher culture-confirmed Salmonella Typhi (16%).…”
Section: Discussionsupporting
confidence: 68%